Telomerase activation in posterior fossa group a ependymomas is associated with dismal prognosis and chromosome 1q gain - Gojo, Johannes; Pajtler, Kristian Wilfried; Hovestadt, Volker; Chavez, Lukas; Korshunov, Andrey; Pfister, Stefan; Kool, Marcel (Neuro-Oncology, 2017)
AbstractBackground. Ependymomas account for up to 10% of childhood CNS tumors and have a high rate of tumor recurrence despite gross total resection. Recently,